In vitro antimicrobial and cytotoxic evaluation of leaf, root, and stem extracts of Solanum dasyphyllum and root and stem extracts of Dovyalis abyssinica - Belitibo, Dereilo Bekere; Meressa, Asfaw; Negassa, Temesgen; Abebe, Abiy; Degu, Sileshi; Endale, Milkyas; Assamo, Frehiwot Teka; Ayana, Temesgen Abdisa; Gurmessa, Getahun Tadesse; Abdissa, Negera (Frontiers in Pharmacology, 2025)
BackgroundPlants like Solanum dasyphyllum and Dovyalis abyssinica have been traditionally used to treat ailments such as fevers, asthma, high blood pressure, infections, stomachaches, skin rashes, for their blood-cleansing and anti-venom properties. Despite their traditional use, limited scientific studies have explored their pharmacological potential, particularly their antimicrobial and anticancer properties.PurposeThis study evaluated in vitro antimicrobial and cytotoxic activities of methanolic extracts from Solanum dasyphyllum (root, stem, and leaf) and Dovyalis abyssinica (root, stem).MethodsSolanum dasyphyllum and Dovyalis abyssinica samples were defatted using n-hexane and subsequently macerated in methanol to obtain crude extracts. Antimicrobial activity was assessed using agar well diffusion and micro-broth dilution methods, while cytotoxicity against the MCF-7 breast cancer cell line was evaluated using the MTT assay. Quantitative analyses of total phenolic and flavonoid contents were carried out using standard spectrophotometric assays.ResultsBoth plant extracts showed strong antibacterial activity, with MIC values ranging from 0.195 to 3.125 mg/mL against all tested strains. S. epidermidis, E. coli, and P. aeruginosa were especially susceptible, with MICs as low as 0.195 mg/mL for Solanum dasyphyllum root and stem and Dovyalis abyssinica root extracts. The Solanum dasyphyllum root extract also exhibited antifungal activity against T. rubrum (inhibition zone 20.67 mm). The root extract of Dovyalis abyssinica showed the highest cytotoxicity against MCF-7 breast cancer cells (IC50 = 0.67 μg/mL), outperforming doxorubicin (IC50 = 3.43 μg/mL).ConclusionThe methanolic extracts of both plants exhibited significant in vitro antibacterial, antifungal, and cytotoxic activities. Notably, the root extracts of both Solanum dasyphyllum and Dovyalis abyssinica, along with the stem extract of S. dasyphyllum, demonstrated strong antibacterial effects. The root extract of D. abyssinica showed remarkable cytotoxicity against MCF-7 breast cancer cells (IC50 = 0.67 μg/mL), outperforming the standard chemotherapeutic agent doxorubicin. These findings highlight its potential as a promising lead for anticancer drug development. Further studies are warranted to isolate the active constituents and confirm their therapeutic efficacy through in vivo investigations and clinical trials.